2016
DOI: 10.1590/1519-6984.05915
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of elemental composition and natural abundance of stables isotopes of C and N in soils and leaves of mangroves at their southernmost West Atlantic range

Abstract: Mangrove communities were selected in the state of Santa Catarina, Brazil, near their southernmost limit of distribution, to study mineral nutrient relation in soils and plants. Communities included three true mangrove species, Rhizophora mangle, Laguncularia racemosa and Avicennia germinans, and two associated species, the fern Acrostichum danaeifolium, and the grass Spartina densiflora. The sites included communities in the lower Río Tavares near Florianopolis city, Sonho beach near Palhoça city, and the San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…They also showed freshwater inputs for these mangrove compartments. A Santa Catarina, Brazil Tognella et al [ 42 ] study showed values of −12.7 to −26.4‰, representing salinity stress in that area.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed freshwater inputs for these mangrove compartments. A Santa Catarina, Brazil Tognella et al [ 42 ] study showed values of −12.7 to −26.4‰, representing salinity stress in that area.…”
Section: Discussionmentioning
confidence: 99%